Voltage Stability Analysis of Power System with Photovoltaic Power Plant - Adrianti Adrianti; Rada Tamara Putri; Muhammad Nasir (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
Photovoltaic power plants usually do not provide reactive power output; hence the application of large photovoltaics in power systems will decrease the voltage stability level of the power system. Capacitor banks can provide reactive power to compensate the photovoltaic plants; therefore, capacitor banks can overcome the reactive power deficiency of photovoltaic plants. However, the effect of capacitor bank installation on the system’s voltage stability is unknown.  Therefore, the research aims to investigate whether installing a capacitors bank can restore the level of system voltage stability. The study employs the method of Voltage Stability Margin and transient stability simulation to the IEEE 9 bus system. The IEEE 9 bus system is modified where one generator of the system is replaced with a photovoltaic plant, and a capacitor bank is also installed. The study results show that the modified system voltage stability level is lower than the original system. When the capacity of the capacitor bank is increased to the maximum allowable value, the voltage stability level rises. However, it is still unable to be restored to its original value.